Holocene activity and seismic surface rupture zone of the Abuduo fault eastern Tibetan Plateau - Liao, Cheng; Liang, Mingjian; Chen, Han; Mao, Zebin; Wu, Weiwei; Gong, Yue; Zuo, Hong; Liu, Shuhuai; Li, Tian; Li, Zhongyang (Frontiers in Earth Science, 2024)
The Garzê–Yushu fault is a large active NW-trending strike-slip fault on the Tibetan Plateau, along which strong earthquakes have frequently occurred historically. Together with the Xianshuihe fault, the Garzê–Yushu fault constitutes the northern boundary of the Sichuan–Yunnan block, and it is also the boundary between the Bayan Har and Qiangtang blocks. The Abuduo fault is a near E–W-trending fault on the southern side of the Garzê–Yushu fault. Through remote sensing image interpretation and field seismic geological investigations, this study found a series of left-lateral displacement landforms and well-preserved seismic surface rupture zones along the Abuduo fault, extending over a distance of approximately 65 km from Abuduo through Yushu and Qinghai to Selikou Village. According to the geological and geomorphological evidence, the Abuduo fault is considered a left-lateral strike-slip fault with Holocene activity, which has tectonic conditions suitable for breeding and generating strong earthquakes. Additionally, the eastward extension of the Abuduo fault is likely to intersect the Garzê–Yushu fault and thereby decompose its horizontal sliding deformation.